2013
DOI: 10.1074/jbc.m113.513028
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Bacterial Deacetylase LpxC Bound to the Nucleotide Reaction Product Reveals Mechanisms of Oxyanion Stabilization and Proton Transfer

Abstract: Background: LpxC is a metal-dependent deacetylase essential for lipopolysaccharide biosynthesis. Results: The LpxC reaction product binds an extensive, conserved groove with the 2-amino group positioned in the active site. Conclusion: The product-bound LpxC structure reveals conserved ligand interactions and stabilization of a phosphate mimic of the oxyanion intermediate. Significance: LpxC structures are critical to elucidate the catalytic mechanism and design of novel antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 42 publications
3
62
0
Order By: Relevance
“…The resulting tetrahedral oxyanion intermediate was mimicked by the phosphate ion that was observed in the crystal structure of Ph‐Dac (Figs D and A). The results of a recent study showed similar mimicking employed by the bacterial deacetylase LpxC . The tetrahedral oxyanion intermediate contains two oxygen atoms: one (O1) from the water molecule that attacked the acetyl group, and the other (O2) from the carbonyl oxygen.…”
Section: Discussionmentioning
confidence: 74%
“…The resulting tetrahedral oxyanion intermediate was mimicked by the phosphate ion that was observed in the crystal structure of Ph‐Dac (Figs D and A). The results of a recent study showed similar mimicking employed by the bacterial deacetylase LpxC . The tetrahedral oxyanion intermediate contains two oxygen atoms: one (O1) from the water molecule that attacked the acetyl group, and the other (O2) from the carbonyl oxygen.…”
Section: Discussionmentioning
confidence: 74%
“…[54][55][56][57] The most relevant examples are: i) the 4-(phenylethynyl)benzamide derivatives LPC-004 and CHIR-090, [58,59] the 4-(phenylbuta-1,3-diyn-1-yl)benzamide derivatives LPC-009 and LPC-011, [60] all of which were developed by Chiron and the University of Washington; ii) the difluoromethyl derivative LPC-058 developed by C. -J. Lee et al; [61] iii) the pyridine methylsulfone LpxC-4 (PF-5081090), [62,63] which was discovered by Pfizer; and iv) the cyclopropane derivative ACHN-975 [56] developed by Achaogen (Figure 5). Diverse crystal structures of the LpxC enzyme from different species, including P. aeruginosa, [59,63,[65][66][67][68][69] Aquifex aeolicus, [67,[70][71][72][73][74][75] Yersinia enterocolitica [76] and E. coli, [52,77] have been solved, either as an apo-form or in complex mainly with inhibitors and these structures provide a good understanding at the molecular level of the differences in the inhibitory potency observed experimentally. The identification of these lead compounds was the result of the synthesis of a very large number of compounds in which mainly diverse moieties that mimic the fatty acid chain of the substrate were explored.…”
Section: The Lpxc Enzymementioning
confidence: 99%
“…Several models of LpxC catalysis have been proposed based on metal substitution, mutagenesis, structural, and pH dependence studies [37-44]. The emerging view implicates E73 as the catalytic general base for deprotonation of the catalytic Zn 2+ -bound water ( Fig.…”
Section: Lpxcmentioning
confidence: 99%